Characterization of a ligand-gated cation channel based on an inositol receptor in the silkworm, Bombyx mori. (July 2016) - Kikuta, Shingo; Endo, Haruka; Tomita, Natsuo; Takada, Tomoyuki; Morita, Chiharu; Asaoka, Kiyoshi; Sato, Ryoichi
Abstract: Insect herbivores recognize non-volatile compounds in plants to direct their feeding behavior. Gustatory receptors (Gr) appear to be required for nutrient recognition by gustatory organs in the mouthparts of insects. Gr10 is expressed in Bombyx mori ( BmGr10 ) mouthparts such as maxillary galea, maxillary palp, and labrum. BmGr10 is predicted to function in sugar recognition; however, the precise biochemical function remains obscure. Larvae of B . mori are monophagous feeders able to find and feed on mulberry leaves. Soluble mulberry leaf extract contains sucrose, glucose, fructose, and myo -inositol. In this study, we identified BmGr10 as an inositol receptor using electrophysiological analysis with the Xenopus oocyte expression system and Ca 2+ imaging techniques using mammalian cells. These results demonstrated that Xenopus oocytes or HEK293T cells expressing BmGr10 specifically respond to myo -inositol and epi -inositol but do not respond to any mono-, di-, or tri-saccharides or to some sugar alcohols. These inositols caused Ca 2+ and Na + influxes into the cytoplasm independently of a G protein-mediated signaling cascade, indicating that BmGr10 is a ligand-gated cation channel. Overall, BmGr10 plays an important role in the myo -inositol recognition required for B . mori larval feeding behavior. Graphical abstract: Highlights: Mulberry leaf extract contains sucrose, glucose, fructose, and myo -inositol. BmGr10 is mainly expressed in maxillary palp in B . mori . BmGr10 expressing cells responded to myo -inositol and epi -inositol.